Collective response to the student reading crisis: Hegemonic and fatalistic counter-narratives in the cyberspace - Shulhan; Hairus Sodik; Moh Zainol Kamal; Hasan Asy'ari Najmuddin (12 Waiheru, 2026)
This study examines how Indonesia’s literacy crisis was constructed within digital public discourse following the viral circulation of a YouTube news segment depicting a junior high school student unable to read. Although literacy decline is commonly framed as a pedagogical issue, limited studies have explored how online publics negotiate responsibility for educational failure in digital spaces. Using a qualitative netnographic approach, this study analyzed 189 public comments extracted from the viral video “Miris, Pelajar SMP Belum Bisa Membaca” by tvOneNews. Data were analyzed through Critical Discourse Analysis to identify dominant attribution patterns and processes of meaning construction. The findings reveal that digital public discourse surrounding literacy decline was shaped by fragmented and competing explanatory frameworks. Structural criticism directed toward curriculum reform, weakened evaluation systems, educational bureaucracy, and state governance frequently coexisted with individualized narratives emphasizing student discipline, parental responsibility, and excessive smartphone use. Public comments also reflected ambivalent perceptions toward teachers, who were simultaneously criticized for bureaucratic orientation and recognized as actors constrained by institutional regulation. Digital technology was framed as a symbolic threat to literacy culture, reflecting broader anxieties regarding educational decline. This study argues that online discourse surrounding literacy crises should not be interpreted as a coherent expression of collective critical consciousness, but rather as a dynamic arena of meaning negotiation shaped by emotional communication and competing interpretations of educational responsibility. The study contributes to digital discourse and critical literacy by extending literacy analysis beyond classroom-centered perspectives toward the sociocultural construction of educational crises within contemporary digital public.